Active methodology of teaching on Legal and Forensic Odontology. Experience in a Public University of Nicaragua. Quali-quantitative - Espinoza Palma, Alicia (2021)
This article aims to assess student’s perception in the implementation of active methodologies for teaching on Legal and Forensic Dentistry, from their own perspective. A mixed methodology study was carried out, considering 57 students who participated in this course and 5 key informants from previous years. The qualitative approach was developed through in-depth interviews and reductionist interpretative analysis and a descriptive study. Results: The students had a positive evaluation for course development with practical activities and it was valued as "Good"; expectations at the beginning were high and were satisfied at the end of course, valued as "Good". The qualitative approach showed a change in expectations regarding the methodology used in previous years.